Pertumbuhan dan Produksi Tanaman Kacang hijau (Vigna radiata L.) Akibat Pemberian Kompos Kubis dan Pupuk Organik Cair Urine Kambing - Armaniar, Armaniar; Br.Sitepu, Sri Mahareni; Pranata, Rizky Ferdi (JURNAL AGROPLASMA, 2024)
The aim of this research was to determine the response of growth and production of green bean plants (Vigna radiata L.) to the application of cabbage compost and goat urine liquid organic fertilizer. This research method used a factorial Randomized Block Design (RBD), consisting of 16 treatments and 3 replications so there were 48 experiments. The treatments studied were: giving cabbage compost with the symbol "K" which consists of 4 types, namely K0 = 0 kg/plot(control),K1=1kg/plot,K2=2kg/plot and K3=3kg/plot. The provision of liquid organic fertilizer from goaturine with the symbol "K" consists of 4 levels, namely U0=0ml/l water/plot (control),U1=100ml/l water/plot,U2=200ml/ l water/ plot and U3 = 300 ml/ l water/plot. The parameters observed were plant height, flowering age, number of pods per sample, number of pods per plot, production per sample, production per plot and weight of 100 seeds. The results of the research after statistical analysis showed that giving cabbage compost had a very significant effect on plant height, number of pods per sample, number of pods per plot, production per sample and production per plot, had no significant effect on flowering age and weight of 100 seeds, where the best treatment obtained in K3 treatment. (3kg/lot). Providing liquid organic fertilizer with goat urine had a very significant effect on plant height, number of pods per sample, number of pods per plot, production per sample and production per plot, it had no significant effect on flowering age and weight of 100 seeds, where the best treatment was obtained in the U3 treatment (300 ml/l water/plot). The interaction between giving cabbage compost and goaturine liquid organic fertilizer did not have a significant effect on all observed parameters Keywords: compost, goaturine, green beans